Work and Health Correlates of Sleep Quantity and Quality Among Correctional Nurses - Zhang, Yuan (J Forensic Nurs, 2019)
BACKGROUND/OBJECTIVES: The correctional environment exposes nurses to unique physical and psychosocial work stressors, such as inmate violence and safety concerns. Nurses often experience short and poor sleep; however, the quantity and quality of sleep in this specialty practice group of nurses are underexplored. The study objective was to examine a wide range of work and health correlates of sleep quantity and quality in correctional nurses. METHODS: A Web-based survey was administered to nurses within a Northeastern State Correctional Health-care System, covering questions on sleep quantity and quality, working conditions, health outcomes, and work outcomes. RESULTS: Among the 89 correctional nurses who participated, 56.2% reported short sleep duration (≤6 hours/day) and 31.8% reported poor sleep quality. Multivariate Poisson regression modeling suggested that night shift (prevalence ratio [PR] = 1.95, p < 0.05) and single marital status (PR = 2.25, p < 0.05) were significantly associated with increased prevalence of short sleep duration, whereas none of the work and health variables were significantly associated with increased prevalence of poor sleep quality, after adjustment for sociodemographics and other covariates. CONCLUSION: Correctional nurses experience a high prevalence of short and poor sleep. Similar to previous studies, we found that short sleep duration was associated with night shift work. Interventions targeting work schedule remodeling (e.g., reduce the number of consecutive night shifts) and shift work coping mechanisms may promote sleep health of correctional nurses.